The grapevine ABC transporter B family member 15 is a trans-resveratrol transporter out of grapevine cells - Martínez-Márquez, Ascensión; Martins, Viviana; Sellés-Marchart, Susana; Gerós, Hernâni; Corchete, Purificación; Bru-Martínez, Roque (Frontiers in Plant Science, 2025)
Stilbenes, particularly trans-resveratrol, play a highly relevant defense role in grapevines as phytoalexin is induced in response to stress. Metabolism and transport of stilbenes can be conveniently investigated in grapevine cell culture since large amounts of trans-resveratrol are accumulated in the extracellular medium upon treatment with the elicitor methylated cyclodextrin, either alone or combined with methyl jasmonate. A proteomic approach on grapevine cell membrane fractions was performed to find trans-resveratrol transporter candidates. The candidate VvABCB15 was functionally characterized. Its stable expression in both yeast and Silybum marianum cells’ heterologous systems led to increased trans-resveratrol transport in these hosts. Transient expression in Vitis cells showed an enhanced absorbent- or elicitor-assisted accumulation of extracellular trans-resveratrol in VvABCB15-expressing or VvGSTU10/VvABCB15-co-expressing cell suspension cultures. Experiments of transient expression in Vitis cell suspensions using light-switchable stilbene synthase (pHYH::VvSTS3) and VvABCB15 further confirmed the candidate’s role as a trans-resveratrol transporter. VvABCB15-YFP fusion proteins in Nicotiana leaf showed localization in the plasma membrane, consistent with a functional role in trans-resveratrol transport. This is the first report to provide evidence for the involvement of an ABC transporter B type, VvABCB15, in trans-resveratrol transport to the extracellular medium of grapevine cells.